Homophobia in Marlowe’s Edward II Homophobia in Marlowe’s Edward II - Gelson Peres de Silva (Ilha do Desterro, 2008)
Drawing on queer theory, this essay demonstrates how
homophobia motivates the plot of usurpation in Edward II, by
Chistopher Marlowe (1564-1593), a play in which complex power relations can be verified. The main characters, King Edward II, Pierce of Gaveston, Mortimer Junior, Mortimer Senior and Queen Isabella, together with the nobles and the clerics, interact in a world of fierce political dispute. Power relations are at the core of the play and involve,
on the one hand, the characters who envy and dispute Edward II’s royal power. On the other hand, the king suffers the effects of the power of his own homosexual drive and affective ties with Gaveston. Drawing on queer theory, this essay demonstrates how
homophobia motivates the plot of usurpation in Edward II, by
Chistopher Marlowe (1564-1593), a play in which complex power relations can be verified. The main characters, King Edward II, Pierce of Gaveston, Mortimer Junior, Mortimer Senior and Queen Isabella, together with the nobles and the clerics, interact in a world of fierce political dispute. Power relations are at the core of the play and involve,
on the one hand, the characters who envy and dispute Edward II’s royal power. On the other hand, the king suffers the effects of the power of his own homosexual drive and affective ties with Gaveston.